Analisis Saluran Pemasaran Ubi Kayu Varietas Malang 1, Malang 4 Dan Adira 1 Di Kecamatan Pallangga Kabupaten Gowa - Harfina, Harfina; Salam, Muslim; Fudjaja, Letty (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The purpose of this research is to study the channels, margins and marketing efficiency in each cassava marketing channel in Pallangga District, Gowa Regency. The method used in collecting primary data is a survey method by conducting direct observations in the field and filling out questionnaires through direct interviews with cassava farmers who are respondents. The determination of the sample was done deliberately (purposive sampling). This descriptive method is used to describe qualitatively the marketing conditions of cassava in Pallangga District, Gowa Regency and to analyze marketing channel patterns. And the results of this study show that for the Malang 4 variety there are 3 marketing channels where the first channel I: Cassava Farmers - Factory, second channel II: Cassava Farmers-Agents - Factory, third channel III: Cassava Farmers - Traders collectors – Factory. Channel I has no marketing margin and 100% Farmer Share with 0% efficiency level, total marketing margin for channel II is IDR 250/Kg and Farmer Share is 80% with 20% efficiency level, total marketing margin for channel III is IDR. 250,-/Kg and Farmer Share of 80% with an efficiency level of 20% so that it can be said that all marketing channels for the Malang 4 variety are efficient. Channel I has no marketing margin and Farmer Share is 100% with an efficiency level of 0%, channel II's total marketing margin is IDR 3,000/Kg and Farmer Share is 57% with an efficiency level of 42% less efficient, channel III's total marketing margin is Rp.2,500,-/Kg and a Farmer Share of 53% with an efficiency level of 46% is less efficient so that it can be said that the first marketing channel for Malang 1 and Adira 1 varieties is efficient.